TRANSIENT HEATING AND CHONDRULE FORMATION: EVIDENCE FROM SODIUM LOSS IN FLASH HEATING SIMULATION EXPERIMENTS - ENERGETICS AND LENGTH SCALES - Yu Y.; Hewins R.H. (My University, 1998)
Flash heating simulation experiments have been performed to determine the effects of heating time, cooling rate, ambient gas fO2, and the sample bulk composition on the extent of Na loss of silicate melts and the implications for chondrule formation. The samples studied include type IA, IAB, and IIAB chondrule analog compositions as well as other synthetic silicate materials. The following experimental conditions were employed: heating temperatures ranging from 1300 to 1750°C, heating times ranging from less than 1 min to 3 h, initial cooling rates ranging from 480°C/h to over 5000°C/h, and ambient gas fO2 ranging from 0.5 to 4 log units below the iron-wustite buffer.Bulk chemical analyses of the experimental charges show that compared to prolonged isothermal heating, flash heating with heating times of less than one minute dramatically reduced Na loss. However, the amount of Na retained by the charge depends greatly on the cooling rate following the heating at the peak temperature, ambient oxygen fugacities, and chondrule compositions. Generally speaking, shorter heating time, higher cooling rate, higher fO2, and a relatively Si-rich and Mg-poor composition favor Na retention.For type IIAB chondrule compositions, experiments show that with an fO2 close to that indicated by natural mineral assemblages (about 10-11.5 to 10-12 atm or higher at 1400°C), the flash heating events can reproduce chondrule textures and Na contents well. With peak heating temperatures of 1400-1750°C, 90% Na retention for type IIAB composition requires a heating time of less than one minute followed by initial cooling rates from ~500°C/h to ~5000°C/h. This result supports the flash heating model to form type II chondrules and implies that if they were formed in a nebular environment, it was dust and/or H2O enriched.Type I chondrule compositions lose Na more easily than type II chondrules under the same heating conditions, probably because of their higher Mg/(Si + Al) ratios. This, plus the lower fO2 environment (10-14 atm or lower at 1400°C) compared to that for type II chondrules, makes it difficult for type I chondrules to retain most of their original Na content and perhaps other volatile elements during the course of their formation, even if the heating was transient in nature. However, type I chondrules are not evaporative residues of type II chondrules. The differences in initial Na contents and other properties, such as refractory elements as well as oxygen fugacities between type I and type II chondrules imply that they probably were formed in different settings in the nebula with somewhat different precursor materials.